2006
DOI: 10.2486/indhealth.44.304
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Blood Lead Levels to Blood Pressure in Exhaust Battery Storage Workers

Abstract: Several researches has focused the hypothesis that low blood lead levels could be associated with an increased risk of hypertension. To assess the relation between occupational lead exposure and elevated blood pressure a group of 27 workers, age range from 27 to 62 years, mean (SD) 36.52 ( 8.16) yr; length of employment mean (DS) 2.97 ( 1.67) yr, were recruited as study subjects. The following variables were measured: blood lead concentration (BPb), δ-Aminolevulinic Acid Dehydratase (ALAD) activity, Zinc Proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
3
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 17 publications
1
19
3
2
Order By: Relevance
“…It is reported that long term occupational exposure to lead is related to a slight increase of systolic and diastolic blood pressure among workers who had been exposed to higher level of lead with respect to workers exposed to lower levels of lead [21,22]. Schuhmacher [23] showed a significant rise of blood pressure with the increases in blood lead levels in 36 male subjects who were occupationally exposed to lead.…”
Section: Discussionmentioning
confidence: 97%
“…It is reported that long term occupational exposure to lead is related to a slight increase of systolic and diastolic blood pressure among workers who had been exposed to higher level of lead with respect to workers exposed to lower levels of lead [21,22]. Schuhmacher [23] showed a significant rise of blood pressure with the increases in blood lead levels in 36 male subjects who were occupationally exposed to lead.…”
Section: Discussionmentioning
confidence: 97%
“…Human studies have generally provided less conclusive evidence for the role of lead and/or cadmium in hypertension 24) . It has been reported that long-term occupational exposure is related to a slight increase in both systolic and diastolic blood pressure 25) . As in similar studies evaluating the effect of lead exposure on blood pressure 26) , our study showed that there was no significant relationship between blood lead levels and systolic and/or diastolic blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have reported the effect of Pb-B on cardiovascular functions, such as blood pressures and peripheral blood flow [2][3][4]7) . Finger blood flow decrease among workers exposed to lead 5) .…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have reported significant relationships between blood lead at low levels and cardiovascular and/or peripheral arterial disease 5,6) , impaired renal function, and elevated blood pressure [7][8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%